Acupuncture in the emergency department for pain management: A BraveNet multi-center feasibility study. Issue 9 (4th March 2022) - Dusek, Jeffery A.; Kallenberg, Gene A.; Hughes, Robert M.; Storrow, Alan B.; Coyne, Christopher J.; Vago, David R.; Nielsen, Arya; Karasz, Alison; Kim, Ryung S.; Surdam, Jessica; Segall, Tracy; McKee, M. Diane
Abstract: Purpose: Pain accounts for up to 78% of emergency department (ED) patient visits and opioids remain a primary method of treatment despite risks of addiction and adverse effects. While prior acupuncture studies are promising as an alternative opioid-sparing approach to pain reduction, successful conduct of a multi-center pilot study is needed to prepare for a future definitive randomized control trial (RCT). Methods: Acupuncture in the Emergency Department for Pain Management (ACUITY) is funded by the National Center for Complementary and Integrative Health. The objectives are to: conduct a multi-center feasibility RCT, examine feasibility of data collection, develop/deploy a manualized acupuncture intervention and assess feasibility/implementation (barrier/facilitators) in 3 EDs affiliated with the BraveNet Practice Based Research Network. Adults presenting to a recruiting ED with acute non-emergent pain (e.g., musculoskeletal, back, pelvic, noncardiac chest, abdominal, flank or head) of ≥4 on a 0-10-point Numeric Rating Scale will be eligible. ED participants (n = 165) will be equally randomized to Acupuncture or Usual Care. At pre-, post-, and discharge time-points, patients will self-assess pain and anxiety using the Numeric Rating Scale. Pain, anxiety, post-ED opioid use and adverse events will be assessed at 1 and 4 weeks. Opioid utilization in the ED and discharge prescriptions will be extracted from patients' electronic medical records. Acupuncture recipients will asked to participate in a brief qualitative interview about 3 weeks after their discharge. ED providers and staff will also be interviewed about their general perspectives/experiences related to acupuncture in the ED and implementation of acupuncture in ACUITY. Results: Recruitment began on 5/3/21. As of 12/7/21: 84 patients have enrolled, the responsive acupuncture intervention has been developed and deployed, and 26 qualitative interviews have been conducted. Conclusion: Successful conduct of ACUITY will provide the necessary framework for conducting a future, multi-center, definitive RCT of acupuncture in the ED. Clinical Trials.gov: NCT04880733 https://clinicaltrials.gov/ct2/show/NCT04880733